Printmaking / Prof. Madya Mohd Suhaimi Tohid - Tohid, Mohd Suhaimi (National Design Center (NDC), 2021)
Printmaking is traditionally produced through images that are printed on a surface such as iron plates, copper, zinc, wood and others through pressure. This process can be repeated to produce an edition. When the ink is placed on a surface that has been scratched, engraved etc. then the ink will be transferred onto the paper. The basics of the printmaking are process relief, intaglio, planographic techniques and paper stencils. New innovations in printmaking include 2D, 3D and 4D computers, broadcast media (television), fine art Photography and time-based media, in line with the latest technology developments.The latest technology that is rapidly evolving is causing change after change that is happening rapidly in the development of Malaysia’s printmaking history. Printmaking is one of the main offerings to students in fine arts majors involving undergraduate and postgraduate levels. For this semester, there are a total of 20 students majoring in printmaking, where each student has to produce 5 works. Each student will present an idea and then translate it through terms of art concept, media, form, content and context.